Atividades antimicrobiana e enzimática do fungo Formitopsis sp. - Chaves, Jéssica Varela (2017)
Fungi produce several bioactive bio-molecules to survive in nature. Some species have economic interests, being source of antibiotics, enzymes, vitamins and steroids. Fomitopsis is a mushroom of great economic value, mainly in Asian continent, due to its ability to produce antimicrobial substances and enzymes. The present work aims to evaluate antimicrobial and enzymatic activities from CBA-452 fungus. A phylogenetic tree was made for identifying fungal isolate at specie level. Antibacterial activity was evaluated by disc diffusion method. Human pathogenic bacteria used as test were Staphylococcus aureus, Streptococcus pneumoniae, Klebsiella pneumoniae and Escherichia coli. Isolated extracts were obtained by liquid-liquid partition with low, medium and high polar solvents using hexane, ethyl acetate and n-butanol until exhaustion, respectively. Extracts were analyzed by thin layer chromatography (CCD). As developers, iodine fume, iron chloride, aluminum chloride, 10% KOH, dragendorf, DPPH (diphenyl-picrylhydrazyl), cerium sulfate, bourchardt and ultraviolet light (254 and 365 nm) were used. Then, a bioautography test was performed for selecting bioactive substances. Enzymatic potential was evaluated cultivating fungus in amylase and cellulase medium at 28°C, and after seven days of enzymatic degradation a halo was formed around the colony, being developed through iodine and lugol solution, respectively. Sequence of fungal isolate had 99.8% of similarity with Fomitopsis durescens specie, and its ethyl acetate extract presented antimicrobial activity against the standard strain of Staphylococcus aureus. Thus, it also proved to be a producer of two enzymes of biotechnological interest, amylase and cellulase, with enzymatic index 0.52 for amylolytic activity and of 1.02 for cellulolytic activity. Despite there is unidentified bioactive substances in bioautography, this study showed that Fomitopsis may be a good source of metabolites with industrial interest, being necessary more studies on this genus in Brazil. Key-words: Basidiomycetes. Bioactivity. Antimicrobial compounds. Hydrolytic enzymes.